Effect of Shield-Tunnel Construction on the Horizontal Response of Adjacent Piles in a Silty Layer - Shuai Zhang; Xue Zhang; Xuan Ning; Haiyun Lu; Minmin Jiang; Shiguang Wei; Xulian Xiao (Buildings, 2023)
This paper studies the problem of shield tunnels laterally passing through piles based on in situ tests and numerical methods. The effects of vertical load, pile–tunnel distance, and tunnel-cover depth on the horizontal displacement and the bending moment of adjacent piles were investigated. The results show that the shield tunnel induced adjacent pile displacement toward the tunnel side near the tunnel axis, and the soil below and above the tunnel axis constrained the pile, displacing toward the tunnel side. The maximum values of the horizontal displacement and bending moment were at the tunnel axis. The vertical load on the cap had little influence on the horizontal response of the pile. The main influence area induced by shield construction was located within 1.5 times the tunnel diameter. The maximum horizontal displacement and maximum bending moment were reduced by 36–45% and 45–78% on the far pile due to the shading effect induced by the near pile. The tunnel-cover depth had a significant influence on the distribution patterns of the horizontal displacement and the bending moment. The positions of the maximum horizontal displacement and the maximum bending moment moved downward with increases in tunnel-cover depth. The maximum horizontal displacement and bending moment increased with increases in tunnel-cover depth.